2021
DOI: 10.3390/electronics10060674
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Workflow for Tumour Detection in Breasts Using 3D Microwave Imaging

Abstract: A two-stage workflow for detecting and monitoring tumors in the human breast with an inverse scattering-based technique is presented. Stage 1 involves a phaseless bulk-parameter inference neural network that recovers the geometry and permittivity of the breast fibroglandular region. The bulk parameters are used for calibration and as prior information for Stage 2, a full phase contrast source inversion of the measurement data, to detect regions of high relative complex-valued permittivity in the breast based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In [33] we showed the ability of this network architecture to accurately predict p 4 (permittivity and geometry) of symmetric fibroglandular regions (Figure 3) from noisy synthetic data, and showed that the combination of adipose and fibroglandular tissues can be used as an appropriate background for tumor detection. In our previous attempts to recover the same parameters from calibrated experimental data for the same symmetric fibroglandular phantom used in this work we were able to accurately recover geometry information, but struggled to recover reasonable estimates for the permittivity of the fibroglandular tissue.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…In [33] we showed the ability of this network architecture to accurately predict p 4 (permittivity and geometry) of symmetric fibroglandular regions (Figure 3) from noisy synthetic data, and showed that the combination of adipose and fibroglandular tissues can be used as an appropriate background for tumor detection. In our previous attempts to recover the same parameters from calibrated experimental data for the same symmetric fibroglandular phantom used in this work we were able to accurately recover geometry information, but struggled to recover reasonable estimates for the permittivity of the fibroglandular tissue.…”
Section: Resultsmentioning
confidence: 94%
“…Full details on the neural network and the overall proposed workflow are presented in our previous work [33], but are summarized here for convenience.…”
Section: Machine Learning Enabled Parametric Inversionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages of CNN-based learning include improved computational efficiency, especially when solving inverse scattering problems. Examples of studies that used machine learning and deep learning neural networks to simplify the inverse problem are given in [ 102 , 118 , 119 , 120 , 121 ]. In addition, a 2D-based imaging algorithm may not work for a 3D biological object and might lead to inaccurate reconstruction results.…”
Section: Challenges and Future Research Directionsmentioning
confidence: 99%